PERBANDINGAN PHONEGAP DAN REACT NATIVE SEBAGAI FRAMEWORK PENGEMBANGAN APLIKASI MOBILE - Dwi Wijonarko; Rizal Fathoni Aji (LPPM STMIK Lombok, 2018)
Mobile application development was growing very rapidly along the increase of mobile devices and technology. One of the problems faced is the different platforms operating system on the market, it is make more difficult development process and requires a lot of cost. An application must be built at least 2 (two) types according to the current popular operating system (Android and iOS) in order to be able to get large application users.Hybrid Application is an application development model that combines native application approach and web application to be a mobile application. It can be converted into more than one mobile operating system platform later. The advantages of hybrid applications is the rapid development process because one source code can run on more than one mobile operating system, while the disadvantage is it use more of resources than the application built with the original language of the operating system platform used.Adobe Phonegap (Phonegap) and React Native are two frameworks that can be used to build mobile hybrid applications. In this study will be compared in terms of development and application results that run on Android devices from each framework by using case studies Aplikasi Jadwal dan Nilai pada Politeknik Kota Malang.